Users' evaluation of the University of the Philippines Institute of Library Science (UP ILS) Library book collection with implications for collection development - Nandwani, Ruel M. (1998)
This study seeks to find out the needs of the graduate and undergraduate students of the University of the Philippines Institute of Library Science and their assessment of the library's book collection to serve as a guide to book collection development for the UPILS library. The findings are divided into: faculty's evaluation, students' evaluation, UPILS list of reserve books and UPILS book collection versus the PAARL standards.